The Effect Of Product Innovation And Price On Competitive Advantage In Umkm Ayam Geprek In Bireuen - Maulana, Rizkha; Zuhra, Fatimah; Murniyanti, Sri; Karimi, Karimi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to determine the effect of product innovation and price on competitive advantage in UMKM of geprek chicken in Bireuen. This type of research is quantitative associative descriptive research by distributing questionnaires to 87 respondents, while the population used in this study were consumers of Ratu geprek chicken. The data analysis tool used in this study used SPSS, Multiple linear regression analysis, hypothesis testing using partial significant test (t-test), simultaneous significant test (F-test), and determination coefficient testing (R2). The results showed that product innovation and price had a positive and significant effect on competitive advantage both simultaneously and partially.